1994
DOI: 10.1177/095441199420800102
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and Stress Analysis of Supported Buttock Contact

Abstract: Non-linear finite element analysis has been used to investigate the contact problem between a buttock and a cushion of varying properties. The buttock tissue has been modelled on the macroscale by assuming it to be a hyperelastic (rubber-like) material with properties that correspond to the overall buttock response. Both rigid and $exible cushions have been considered. The contact between the cushion and the buttock has been modelled assuming both friction and friction-jiree conditions. The effect of these par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 10 publications
6
48
1
Order By: Relevance
“…Several such FE models have been developed [9], [11], [13], [15]- [19]. However, several intrinsic weaknesses are associated with these models.…”
Section: Introductionmentioning
confidence: 99%
“…Several such FE models have been developed [9], [11], [13], [15]- [19]. However, several intrinsic weaknesses are associated with these models.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several attempts in using FE analysis to evaluate sitting induced mechanical response in deep tissue of the buttocks [5][6][7]11,19,23,24]. Chow and Odell (1978) [6], using a simple axi-symmetric buttock FE model, found that the buttock tissue experienced small deformation when using a floating support design cushion.…”
Section: Discussionmentioning
confidence: 99%
“…Chow and Odell (1978) [6], using a simple axi-symmetric buttock FE model, found that the buttock tissue experienced small deformation when using a floating support design cushion. Dabnichki et al (1994) [7], employing contact elements in a simple 2D FE buttock model, found that the maximal compressive stress and displacement generated close to the bony prominences depended on the surface conditions, with the rough compliant surface generating the least compressive stress and tissue deformation. Oomens et al (2003) [19], using a simple 2D FE model, also studied the mechanical responses of the deep tissues related to cushion properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations